The Effect of Long‐Term Relocation on Child and Adolescent Survivors of Hurricane Katrina. Issue 5 (24th September 2013) - Hansel, Tonya C.; Osofsky, Joy D.; Osofsky, Howard J.; Friedrich, Patricia
<x xml:space="preserve">Abstract</x> The current study is designed to increase knowledge of the effects of relocation and its association with longer‐term psychological symptoms following disaster. Following clinical observations and in discussions held with school officials expressing concerns about relocated students, it was hypothesized that students who relocated to a different city following Hurricane Katrina in 2005 would have more symptoms of posttraumatic stress compared to students who returned to New Orleans. The effect of Hurricane Katrina relocation was assessed on a sample of child and adolescent survivors in 5th through 12th grades (N = 795). Students with Orleans Parish zip codes prior to Hurricane Katrina were categorized into relocation groupings: (a) relocated to Baton Rouge, (b) returned to prior zip code, and (c) moved to a different zip code within Orleans Parish. Overall results revealed more trauma symptoms for relocated students. Results also revealed that younger relocated students had fewer symptoms compared to older students. The opposite was found for students who returned to their same zip code, with older students having fewer symptoms. This study supports the need for school‐based services not only in disaster areas, but also in schools where survivors tend to migrate.